17.1k views
5 votes
Solve by completing the square t² - 6t = 7

2 Answers

5 votes

Answer:

T = 7

Explanation:

How you find T is by multiplying different numbers and squaring them by subtracting until you get to the number that equals to 7

User Sologoub
by
5.1k points
2 votes

Answer:

t = 7 or t = -1

Explanation:

You can use a calculator or:

t² - 6t = 7

-> t² - 6t -7 = 0

-> t² - 7t + t - 7 = 0

-> t(t-7) + (t-7) = 0

-> (t-7) . (t+1) = 0

-> t = 7 or t = -1

User Christophe Fuzier
by
5.0k points